PENGARUH MOTIVASI DAN KEPUASAAN KERJA TERHADAP KINERJA KARYAWAN DI SNACK BOX SIDAKATON TEGAL : (studi kasus jajan snack box dakaton Tegal) - Sopiatun Hasanah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Sopiatun Hasanah, 2023, The influence of work motivation and job satisfaction on the performance of Snack Mba Fia Sidakaton employees. Snack mba Fia Sidakaton is an MSME located in Sidakaton village, Dukuhturi sub-district, Tegal Regency. Snack mba Fia Sidakaton is an MSME in Tegal district which has many customers from inside and outside the village. Apart from stocking merchandise on site, Ms. Fia Sidakaton snacks also accepts orders for customers. Usually accept orders for celebrations, social gatherings, snacks for school and others The method in this research is a type of quantitative research with the test tool used, namely multiple linear regression analysis. The population in this research is all Snack mba Fia Sidakaton employees, totaling 30 employees using census or saturated sampling. This research uses primary data with a questionnaire data collection method. Based on the results of the f test in this research, it shows that motivation and job satisfaction simultaneously have a significant positive effect on employee performance. The t test results obtained: a) motivation has a significant positive effect on employee performance, b) job satisfaction has a significant positive effect on employee performance. From the results of this research, it can be concluded that motivation and job satisfaction influence the performance of Snack Mba Fia Sidakaton employees